Neoclypeodytes Young from Panama, with description of two new species (Coleoptera: Dytiscidae: Hydroporinae: Bidessini) - Scheers, Kevin; Hájek, Jiří (Zootaxa, 2020)
Minute Bidessini diving beetles of the genus Neoclypeodytes Young, 1967 from Panama are reviewed. Two new species, Neoclypeodytes balkei sp. nov. and N. fortunensis sp. nov. are described from Campana, Panama Province in central Panama, and La Fortuna, Chiriqui province in western Panama, respectively. Both species differ from all congeners by the colour pattern of the elytra and the shape of the male genitalia. Additionally, we provide a short diagnosis, illustrations and a new record for N. curtulus (Sharp, 1882). Furthermore, we report on the presence of scale-like setae at the apex of median lobe of the aedeagus of N. curtulus and N. fortunensis sp. nov., a character not previously observed in Neoclypeodytes species. With the addition of these two new species, there are now three species of Neoclypeodytes known from Panama and south of Guatemala.